HADITH ABOUT LIFELONG LEARNING: A STRATEGY TO ENCOURAGE LONG LIFE LEARNING AMONG THE PEOPLE - Indo Uleng; La Ode Ismail Ahmad; Muhammadiyah Amin; Abd. Bashir Fatmal (International Journal of Islamic Studies, 2025)
In the era of globalization, lifelong learning has become an urgent need due to changes in technology and the job market. However, public participation is still low, especially in developing countries. Islam emphasizes the importance of knowledge, as reflected in the Prophetic traditions that encourage people to continue learning. These hadiths can serve as motivation and strategies to increase community involvement in continuing education. This study aims to examine the role of hadith in promoting lifelong learning and formulate strategies based on Islamic values that can be applied in continuing education. The research method used is a qualitative approach with analysis of hadith texts and literature studies. This study also adopts an interdisciplinary approach by linking hadith studies with modern learning theories. The results show that hadith has great potential in shaping the paradigm of lifelong learning. The integration of hadith with modern learning strategies can increase community motivation and participation. For example, entrepreneurship training can be linked to the hadith on work ethic while digital literacy can be taught through the analogy of the story of Prophet Moses and Prophet Khidir. Initial case studies show that hadith-based approaches are more effective than secular methods in increasing community engagement in learning. Lifelong learning is a fundamental principle in Islam, but it still faces challenges in its implementation. Synergy between academics, government and religious institutions is needed to develop education policies that are more inclusive and based on Islamic values.